Cryoamputation: An old surgical technique to be kept on ice?. (July 2015) - Wordsworth, Matthew; McGuire, Carina; Khan, Mansoor
Cryoamputation is a little known method of delaying a surgical amputation by rapid freezing of the affected limb to prevent further derangement of systemic physiology – hence its historical name of 'physiologic amputation'. Rapid cryoamputation allows for a period of optimisation before surgical amputation in unstable patients. There is limited published literature on the technique and a systematic review was undertaken to identify the techniques, potential indications, complications and potential relevance to current practice and related novel developments. A literature review produced 15 relevant papers that were reviewed; all were either case reports or case series. Cryoamputation can be a lifesaving procedure in a cohort of patients at a high risk of mortality. It is a historical damage control technique and whilst it is unlikely to be used regularly, it is an effective, rapid and simple technique that should not yet be forgotten.